KONSERVASI GENETIK CENDANA BERBASIS PARTISIPASI MASYARAKAT DI DESA NUSA KABUPATEN TIMOR TENGAH SELATAN (Genetic Conservation Of Sandalwood Based On Community Participation In East Nusa Tenggara) - sumardi sumardi (Balai Penelitian Dan Pengembangan Teknologi Hasil Hutan Bukan Kayu, 2017)
Sandalwood (Santalum album Linn.) is a species that has advantages and contribution to the development of East Nusa Tenggara province. It is a commodity that has contributed the highest foreign exchange for the regional income of East Nusa Tenggara Province in 1986/1987 up to 1990/1991. However, the sustainability of sandalwood is now threatened due to mismanagement and low success of regeneration. To avoid the occurrence of genetic degradation or even the extinction of this species is important to do genetic conservation. The community participation model for the genetic conservation of sandalwood has been piloted in the Timor Tengah Utara District of East Nusa Tenggara Province. This study aimed to analyze the success and growth of sandalwood in the model of community participation for genetic conservation strategy of sandalwood in East Nusa Tenggara. The analysis has shown that the survival rate of sandalwood in the genetic conservation with community participation model at 1 year old are 100% if planted on the yard; 90.74% if planted on the bare land; and 64.58% if planted on the land with a very close shade. Trials in 5 farmer groups showed that no significant difference between farmer groups on successful planting in the field, as indicated by similar plant life percentages. Meanwhile, The variance analysis on the growth characteristic showed that mean of high and diameter were not significantly different between treatment model of planting. The mean of height and diameter of each shading treatment were 30.13 cm and 2.97 mm if planted on the yard area; 31.49 cm and 3.25 mm if planted on the bare land; and 29.63 cm and 3.05 mm if planted on the land with a very close shade.